Analyzing the Associations between Facets of Physical Literacy, Physical Fitness, and Physical Activity Levels: Gender- and Age-Specific Cross-Sectional Study in Preadolescent Children - Petra Rajkovic Vuletic; Barbara Gilic; Natasa Zenic; Vladimir Pavlinovic; Marijana Geets Kesic; Kemal Idrizovic; Mirela Sunda; Marko Manojlovic; Damir Sekulic (MDPI AG, 2024)
Physical literacy (PL) is theorized to be an important determinant of physical fitness (PF) and physical activity levels (PALs), but studies have rarely examined possible correlations between PL, PF, and PAL in preadolescent children. This study aimed to evaluate age-specific and gender-specific correlations between the affective and cognitive domains of PL (PLAC), PF, and PAL in preadolescents. Additionally, the test-retest reliability of the applied PF tests was examined. The participants were 107 children (9 to 11 years of age; 53 girls). Apart from gender and school age (third graders, fourth graders), the variables included PLAC, PAL, and PF. PF was evaluated by anthropometrics and body composition indices, sit-ups, push-ups, PACER tests, torso lifts, and broad jump. PLAC was evaluated using the PLAYself questionnaire, and the PAQ-C was used to evaluate PAL. The test-retest reliability of the PF tests was appropriate to high (ICC: 0.65-0.91). Analyses showed nonsignificant associations between PLAC and PAL in both genders and age groups. PAL was significantly correlated with PL in girls (low correlation) and fourth graders (moderate correlation). The nonsignificant associations between PLAC and PF could be a consequence of the influence of biological maturity on PF in this age group. The correlation between PAL and PLAC can be explained by the differences in physical activity habits between genders and age groups, with participation in structured physical activities (organized sports and physical education) being the most important source of PAL in girls and older children.